PELATIHAN PMR DALAM MEMBERIKAN PERTOLONGAN PERTAMA PADA KECELAKAAN DI SEKOLAH - Sugesti Aliftitah; Elyk Dwi Mumpuningtias; Nelyta Oktavianisya (Jurnal Pengabdian kepada Masyarakat, 2023)
Child injury is a health problem whose incidence is increasing and requires special attention. The problem at SMAN 1 Bluto is that 82% of PMR members have sufficient knowledge about First Aid, and 75% have low motivation to implement First Aid in the school environment for reasons of lack of self-confidence and fear of making mistakes when helping victims. The solution to this problem is to carry out PMR training in providing first aid for accidents at school. The method in this PKM is socialization to increase PMR knowledge and the next stage is training in providing first aid for accidents at school. PMR is equipped with a First Aid pocket book. PKM activities were carried out at SMAN 1 Bluto in February-September 2023. The results of this PMR training activity had a good impact, namely that after conducting socialization about First Aid for Accidents at School, the participants' knowledge increased to a high level of knowledge by 95%. The level of participant motivation increased, 90% of participants had high motivation to implement first aid in the school environment.